ANALYSIS OF STUDENT SATISFACTION USING THE E-ASSIGNMENT APPLICATION USING THE WEBQUAL 4.0 METHOD - Sri Restu Ningsih; Elisa Daniati Edison; Hesty Aisyah; M. Tasnim; Nur Azizah; Nurhidayat; Weri Sirait (Yayasan Nuraini Ibrahim Mandiri, 2024)
The very rapid development of information technology has made websites an inseparable part of an educational institution as well as services for the academic community, lecturers, students and education staff. One of the learning applications used for continuity of learning is E-Assignment. E-Assignment is a learning media application that functions to collect and assess student assignments online. The problem that occurs is that there are still students who are not satisfied with using the E-Assignment application. The aim of this research is to analyze and measure the quality of E-Assignment in the lecture process among Metamedia University students. The method used to measure the quality of the E-Assignment website is WebQual 4.0. This research was carried out by utilizing research instruments based on three groups of WebQual 4.0 indicators and then distributing them to students of the Information Systems study program. WebQual 4.0 is an instrument that assesses the quality of a website from the end user's perspective. The tools and applications used to test the relationship between variables from WebQual 4.0 and user satisfaction are SPSS 20 and Matlab. The research results show that the overall score for the WebQual 4.0 indicator obtained is 69% in the Good category, so that users assess that the E-Assignment application is quality as a web learning medium in higher education. Keywords: E-Assignment, WebQual 4.0, SPSS, Matlab